Correlation between duration of untreated psychosis and long-term prognosis in chronic schizophrenia - Yu, Minglan; Tan, Qingyu; Wang, Yan; Xu, Yi; Wang, Tingting; Liu, Dongmei; Chen, Dechao; Deng, Peiying; Huang, Chaohua; Liang, Xuemei; Liu, Kezhi; Xiang, Bo (Frontiers in Psychiatry, 2023)
Objective: To explore the relationship between the Duration of Untreated Psychosis (DUP) and long-term clinical outcome, cognitive and social function in patients with chronic schizophrenia (SCZ). Methods: A total of 248 subjects with chronic SCZ were enrolled in this study, including 156 in the short DUP group and 92 in the long DUP group. The Positive and Negative Symptoms Scale (PANSS), the Brief Negative Symptoms Scale (BNSS), the Global Assessment of Functioning (GAF) scale and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) were used to assess all of the subjects. Results: The negative symptom scores (the PANSS and BNSS) of subjects with long DUP were significantly higher than that in subjects with short DUP. The scores of visual span and speech function in the short DUP group were significantly higher, indicative of decreasing cognitive function with time. In terms of social function, the short DUP group scored higher, with a statistically significant difference. Meanwhile, we found that the length of DUP was positively correlated with the negative symptom score of the PANSS, negatively correlated with visual span scores, and GAF scores. Conclusion: This study demonstrated that the DUP remained a significant association with negative symptom and cognition in long period of chronic SCZ.